2012
DOI: 10.5539/mas.v6n8p52
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factor of Carbon Dioxide from In-Use Vehicles in Thailand

Abstract: The objective of determining the emission factor of carbon dioxide (EF-CO 2 ) from in-use vehicles in Thailand is to gather important data for estimating transport emissions. These data may help develop greenhouse gas management plans for the area. In-use vehicles were tested on a chassis dynamometer by the Bangkok Driving Cycle to quantify CO 2 emissions. The emission factor is defined as the average emission rate for CO 2 per vehicle based on average speed and fuel consumption. The studied vehicle types were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…1.1) CO 2 emission rates from HDD For the HDD with diesel, the CO 2 emission rate was 1,036.4-1,212.9 g km -1 with no significant difference but different vehicle speeds between diesel and NGV were significantly different at 20-40 and 40-80 km h -1 . This result is in accord with the results of previous studies [12][13], which reported that, compared to the proportion of O 2 and N 2 in the fuel, 50 % of the diesel emissions were CO 2 . The average CO 2 emission level was dependent on vehicle speed, as demonstrated by the following results: 1,290.6 ±96.7, 577.3±91.6 and 1,568.4±179.1 g km -1 at 0-20, 20-40 and 40-80 km h -1 , respectively.…”
Section: Results and Discussion 1) Co 2 Emission From Diesel Engine supporting
confidence: 93%
“…1.1) CO 2 emission rates from HDD For the HDD with diesel, the CO 2 emission rate was 1,036.4-1,212.9 g km -1 with no significant difference but different vehicle speeds between diesel and NGV were significantly different at 20-40 and 40-80 km h -1 . This result is in accord with the results of previous studies [12][13], which reported that, compared to the proportion of O 2 and N 2 in the fuel, 50 % of the diesel emissions were CO 2 . The average CO 2 emission level was dependent on vehicle speed, as demonstrated by the following results: 1,290.6 ±96.7, 577.3±91.6 and 1,568.4±179.1 g km -1 at 0-20, 20-40 and 40-80 km h -1 , respectively.…”
Section: Results and Discussion 1) Co 2 Emission From Diesel Engine supporting
confidence: 93%
“…The LDDV had the lowest EF-CH 4 at 0.17 g km −1 and LDGV-2 had the lowest EF-CO 2 at 153.8 g km −1 . The results of this test correspond with the results from the chassis dynamometer in the study by Nilrit and Sampanpanish (2012).…”
Section: Emission Factors Of Ch 4 and Co 2 From The Tests Of The Thresupporting
confidence: 85%
“…Carbon dioxide gas is the main cause of global warming, dust and other particulates are the main causes of haze and other bad weather. These harmful components in the exhaust gas have a direct impact on the environmental and human health of human beings [3][4][5][6]. From the perspective of environmental protection, in order to reduce the emission of automobile exhaust, and thus reduce the pollution to the environment, the development of new vehicles replacing traditional internal combustion engines is the inevitable trend of the future [7][8][9].…”
Section: Introductionmentioning
confidence: 99%